English for Islamic Studies: The Analysis of Syllabus Design and Material Development in EIS Textbook at Language Centre (LBB) of STAIN Kediri - Muhyiddin, Muhammad (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article is intended to raise awareness on the importance of designing syllabus and developing materials of English for Islamic studies appropriately. This sort of English is a kind of English for specific purposes for non-English students. Syllabus design and material development contribute to help students improve their English skills. To enable both lecturers and students to achieve this objective, an appropriate syllabus and material development should be prepared well and designed comprehensively.